2012
DOI: 10.1016/j.ijgo.2012.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a yoga program on glucose metabolism and blood lipid levels in adolescent girls with polycystic ovary syndrome

Abstract: Yoga was found to be more effective than conventional physical exercises in improving glucose, lipid, and insulin values, including insulin resistance values, in adolescent girls with PCOS independent of anthropometric changes. Central Trial Registry of India No.: REFCTRI-2008 000291.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…12 (21), 20 months (22)) duration, focus on specific populations (e.g. South Asians (23,24)) or age groups (25)(26)(27). Interventions varied widely in their activities involved, e.g.…”
mentioning
confidence: 99%
“…12 (21), 20 months (22)) duration, focus on specific populations (e.g. South Asians (23,24)) or age groups (25)(26)(27). Interventions varied widely in their activities involved, e.g.…”
mentioning
confidence: 99%
“…12 (21), 20 months (22)) duration, focus on specific populations (e.g. South Asians (23,24)) or age groups (25)(26)(27). Interventions varied widely in their activities involved, e.g.…”
mentioning
confidence: 99%
“…34 Researches has also reported the effect of yoga program (consisting of Asanas, Pranayama and Dhayna) and conventional physical exercise on glucose metabolism and lipid profile in PCOS subjects after practicing it daily for 1hour for consecutive 12 weeks and found that yoga was more effective than conventional physical exercise in improving glucose, lipid, insulin sensitivity. 35 …”
Section: Yogic Interventionsmentioning
confidence: 99%